Pengaruh Penerapan Sistem Modernisasi Administrasi Perpajakan dan Sanksi Pajak Terhadap Tingkat Kepatuhan Wajib Pajak UMKM (Studi Kasus Wajib Pajak UMKM di Kecamatan Coblong) - Megil Fernanda; Joan Yuliana Hutapea; James Uly Reke (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the effect of implementing the tax administration modernization system and tax sanctions on the level of compliance of UMKM taxpayers in the Coblong sub-district. This research uses 60 samples of UMKM taxpayers as primary data. The data collection method involves distributing questionnaires using the purposive random sampling method. Data were analyzed using multiple linear regression by testing the coefficient of determination (r2), F-test, and T-test. From the results of the t-test, it was found that the tax administration modernization system had an effect on UMKM taxpayer compliance, with a calculated t-value of 3.496 > t-table of 2.00247. The tax sanctions variable also influences MSME taxpayer compliance, with a calculated t-value of 5.608 > t-table of 2.00247. The results of the multiple linear regression significance test obtained an F value of 31.474 with a significance of 0.000. So, the coefficient of the regression equation is significant. The coefficient of determination of 52.5% indicates that modernization of the tax administration system and tax sanctions influenced 52.5% of the decision, and other variables influenced the remaining 47.5%. Keywords: tax admnistrasion modernization system, tax sanctions, UMKM taxpayer complience